Development of a cell-type cylindrical carrot seeder - Marvin T. Valentin; Keithler M. Pagnas; Roger Lee M. Suclad; Algirdas Jasinskas; Rolandas Domeika; Egidijus Šarauskis (Heliyon)
Accurate planting of the required number of carrot seeds is one of the important parameters in developing a carrot seeding device. This study developed a metering mechanism that promotes the deposition of <3 carrot seeds on each planting hill at negligible seed damage. The metering disc and hopper were especifically designed to ensure consistency and uniformity in seed loading into the seed cell and their subsequent efficient discharge onto the planting hills. A key feature of the design is the clearance between the metering disc and the hopper, which was strategically designed to scrape excess seeds from the seed cells, allowing the surplus to freely slide back into the hopper without causing damage. The performance of the seeder was evaluated by examining key parameters, including the number of seeds dropped per hill, scattering index, hill diameter, hill spacing, and missing index across various operating speeds (60, 80, 100, 120, and 140 cm/s). The results demonstrated that the seeder achieved optimal performance at operating speeds between 80–120 cm/s, with an average of 1.70 to 1.81 seeds dropped per hill. Mean hill spacing between hills ranged from 10.98 to 13.50 cm at speeds below 120 cm/s. At a higher speed of 140 cm/s, the mean hill spacing and missing index were 23.06 cm and 53.33 %, respectively. Additionally, the scattering index decreased at a higher operating speed. The developed metering mechanism significantly enhanced the efficiency of the seeder, ensuring precise seed placement and reducing seed wastage across varying operating conditions.